Optimizing Employee Performance in Retail Companies: The Interplay of Adversity Intelligence, Digital Literacy, and Job Satisfaction - Hamdani, Fajri (International Journal of Business, Law, and Education, 2024)
This study examines how adversity intelligence and digital literacy affect retail employee performance in Jakarta, using work satisfaction as a mediator. In the face of severe retail competition, organizations must guarantee that staff have technical skills, problem-solving abilities, and technological adaptability. This quantitative study surveys 250 Jakarta shop workers. The study shows that adversity intelligence and digital literacy improve employee performance, and work happiness mediates the link. These results help HR managers build training programs that promote employee performance by improving adversity intelligence, digital literacy, and work happiness